2004
DOI: 10.1111/j.1752-1688.2004.tb01020.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF REMOTE SENSING IMAGERY SOURCE ON QUANTIFICATION OF RIPARIAN LAND COVER/LAND USE1

Abstract: This paper compares approaches to quantifying land cover/land use (LCLU) in riparian corridors of 23 watersheds in Oregon's Willamette Valley using color infrared aerial photography (AP) and Thematic Mapper (TM) imagery. For each imagery source, LCLU adjacent to stream networks were quantified across a range of lateral and longitudinal scales. Single‐date AP data had higher LCLU class accuracies than the multi‐date TM data, except for row crops. Correlations among LCLU classes for the two imagery sources incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…This is of major importance regarding linear corridors whose structure cannot be correctly described by CLC data. Similar results have been presented in the literature (Lattin et al, 2004;Shuft et al, 1999). It is most likely that, in many situations within river corridors, the generalisation level of the CLC database will lead to under-or overestimation of the effect of cover types which impact on stream chemical and biotic metrics (Goetz, 2006).…”
Section: Comparison Of Land Cover Mapssupporting
confidence: 92%
“…This is of major importance regarding linear corridors whose structure cannot be correctly described by CLC data. Similar results have been presented in the literature (Lattin et al, 2004;Shuft et al, 1999). It is most likely that, in many situations within river corridors, the generalisation level of the CLC database will lead to under-or overestimation of the effect of cover types which impact on stream chemical and biotic metrics (Goetz, 2006).…”
Section: Comparison Of Land Cover Mapssupporting
confidence: 92%
“…Unsurprisingly (and as already demonstrated by Lattin et al, 2004;Hollenhorst et al, 2006;Tormos et al, 2011), a comparison of spatial indicators of land cover from the two data sources showed that highly resolved data (a) (b) Fig. 5 The percentage of the total surface area covered by land in the seven classes (see Table 1 for the aggregated land cover types for each class) in a buffer zone of various widths 3000 m upstream of an example sampling site (located on a second order stream): (a) computed from MSRI-derived data; (b) computed from VHSRIderived data.…”
Section: Discussionsupporting
confidence: 56%
“…Not surprisingly, land use has been found to have a large effect on the amount of nitrogen exported to the stream (Salvia-Castellvi et al, 2005;Schilling, 2002;Jordan et al, 1997;Owens et al, 1991;Howarth et al, 2002;Jordan and Weller, 1996;Johnson et al, 1997;Herlihy et al, 1998;Wernick et al, 1998;Arheimer and Liden, 2000;Jones et al, 2001;Wayland et al, 2003;Donner et al, 2004;Woli et al, 2004;Buck et al, 2004;Lattin et al, 2004;Little et al, 2003). Since a significant portion of nitrogen export from catchments is due to non-point source fertilizer runoff, the proportion of agricultural land in a catchment is often correlated to stream nitrate export (Howarth et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…This may be due to sewage inputs or deposition and subsequent runoff of NO x emissions. The majority of the work on land use effects has focused on baseflow or a small number of sampling events correlating land use and nitrate (Johnson et al, 1997;Herlihy et al, 1998;Wernick et al, 1998;Arheimer and Liden, 2000;Jones et al, 2001;Wayland et al, 2003;Donner et al, 2004;Woli et al, 2004;Buck et al, 2004;Lattin et al, 2004;Little et al, 2003;Schilling, 2002). While it is clear that land use affects the magnitude of nitrate and other nutrients exported from catchments, it is not clear how it affects nutrient dynamics or the nutrient concentration pattern during storm events.…”
Section: Introductionmentioning
confidence: 97%